2002
DOI: 10.1046/j.1439-0531.2002.t01-1-00379.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Stereoscopy, Light Microscopy and Ultrastructural Methods for Evaluation of Bovine Embryos

Abstract: The most important point in embryo transfer success is the evaluation of the stage of development and quality of embryos. Therefore, the purpose of this study was to compare the morphological evaluation of embryos using stereoscopy, light microscopy and electron microscopy in order to establish the accuracy of former method compared with more invasive and accurate procedures. For this purpose, 23 Brahman x Swiss cows were used and synchronized with Norgestomet 6 mg plus, 5 mg Estradiol valerate (Syncromate B(R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
34
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(38 citation statements)
references
References 23 publications
4
34
0
Order By: Relevance
“…Immature oocytes are routinely selected for IVM by visual assessment of morphological features. Although morphological criteria provide a reasonable means of identifying oocyte quality and suitability for IVM, there is evidence that morphological criteria are not suffi cient for selection of oocytes of superior developmental potential (Aguilar et al, 2002;Han et al, 2006;Bols et al, 2007). It was clearly demonstrated that immature oocytes selected by similar morphological features differ in their developmental potential.…”
Section: Introductionmentioning
confidence: 99%
“…Immature oocytes are routinely selected for IVM by visual assessment of morphological features. Although morphological criteria provide a reasonable means of identifying oocyte quality and suitability for IVM, there is evidence that morphological criteria are not suffi cient for selection of oocytes of superior developmental potential (Aguilar et al, 2002;Han et al, 2006;Bols et al, 2007). It was clearly demonstrated that immature oocytes selected by similar morphological features differ in their developmental potential.…”
Section: Introductionmentioning
confidence: 99%
“…In the literature, there is still no consensus as to the optimal development stage for embryo cryotolerance (Saragusty & Arav, 2011). Moreover, embryos classified as good quality, according experienced technicians following established criteria (Lindner & Wright, 1983) showed degenerative stages features under electron microscopy in 30% of the cases (Aguilar et al, 2002). Farin et al (1995) have proved the subjectivity of the stereoscopic evaluation by showing that embryos that were classified as being of high quality by the time they were frozen, were in fact in due process of degeneration when assessed by more accurate techniques.…”
Section: Resultsmentioning
confidence: 99%
“…These results agree with observations by Callesen et al (1995), who reported that embryos evaluated at a more advanced, as opposed to early developmental stages, have better quality and are easier to assess with precision. Aguilar et al (2002) reported up to 30% variability in evaluation criteria being the highest in embryos judged as being of moderate quality. This disagreement in evaluations has also been found in other studies.…”
Section: Discussionmentioning
confidence: 99%